Numerical analysis and ANFIS modeling for mixed convection of CNT-water nanofluid filled branching channel with an annulus and a rotating inner surface at the junction - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2018)
Numerical study for mixed convection of CNT-water nanofluid flow in a branching channel with annulus at the junction and a rotating surface was performed by using finite volume method. This geometry can be used in a variety of engineering applications such as in geothermal, gas pipelines, in pharmaceutical, fuel cells and many others. The numerical simulations are performed for various values of pertinent parameters such as Richardson number, angular rotational velocity of the inner surface at the annulus junction, solid nanoparticle volume fraction and diameter of the inner rotating. It was observed that the recirculation regions established within the annulus and separated fluid zones on the walls of the branching channel near the junction are strongly influenced by the by rotation of the inner surface at the annulus. The average Nusselt number enhancements up to 64% are obtained for the nanofluid containing the highest particle volume fraction for Ri = 0.01 and Ri = 1 when the inclination angle of the lower branching channel is 45 degrees. Finally, ANFIS modeling technique with triangular-shaped membership function and 48 fuzzy rules are used to predict the average Nusselt numbers for the hot walls of the channel and annulus part. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: CNT-nanofluid; Branching channel; Finite volume method; ANFIS